DAMPAK KENAIKAN HARGA MINYAK BUMI TERHADAP PERMINTAAN CPO UNTUK BIODIESEL DAN BEBERAPA ASPEK PADA INDUSTRI KELAPA SAWIT INDONESIA - Purba, Jan Horas Veryady; Hartoyo, Sri (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2010)
ABSTRACTIndonesia is the biggest palm oil producer and exporter in the world. In2008, Indonesia contributed 34.3% of total palm oil world production and 84.6%of production was exported as crude palm oil (CPO).In the worldâs market, the growth of palm oil consumption and importwere 9.66%/year and .34%/year. In supply side, palm oil production and exportincreased 7.94%/year and 9.55%/year respectively. It reflected global excessdemand which influence palm oil price in world market, 1.69%/year. Demand forIndonesian CPO also to fulfill the raw material for energy. This situation willinfluence several aspects in Indonesian palm oil industry, in order to ensure theavailability of palm oil to fulfill national necessity for cooking oil industry and biodiesel industry.By using annual data 1979-2008 periods, an econometric approach wasapplied in this study. The goal of this study is to analyze (a) the analyze thecorrelation between world petroleum oil price with CPO world price, (b) theanalyze the effect of petroleum oil price toward domestic palm oil demand, (c) tosimulate the effect of petroleum oil price for 18,71% toward several aspects inIndonesian palm oil industryThe findings of the study show that (a) since 2000 there was the strongcorrelation between world petroleum oil price with CPO world price, that reflectthat CPO is used for raw material of bio diesel industry; (b) petroleum oil pricepositively influenced domestic palm oil demand, and (c) the rise of worldpetroleum oil price will affect the domestic cooking oil industry, i.e. the cookingoil supply will decrease, and the cooking oil price will increase due to the lack ofCP O for cooking oil industry, while the bio diesel industry was start to grow.Key words: crude palm oil, petroleum oil price, cooking oil, bio diesel